STUDY OF FLOODPLAIN MODELLING BASED ON RISK, CASE STUDY DENGKENG RIVER, KLATEN REGENCY - VIDYA PRADANA (NIM : 25015034), KRISHNA
Failure of the flood control system may be due to various factors, including the uncertainty of the magnitude of the flood discharge of the plan resulting in the capacity of the system to be exceeded from the calculated. The existence of the uncertainty factor is recognized as a serious issue in hydrological studies. While the accuracy of the flood discharge flood plan from the flood control system is one of the successful factors in reducing flood risk in the flood plain area. Flood risk analysis involves hydrological and hydraulic inputs. Hydrological and hydraulic modeling is influenced by many sources of uncertainty such as input data, model structure, and model parameters. In hydrological modeling the selection of models and parameters corresponding to a watershed should be evaluated by the hydraulic model in the river as a measured discharge distributor. The river cross-sectional capacity is the first defense in knowing the reliability of a flood plain. The capacity of the river is also a description of the potential magnitude of the risk of possible flooding. This floodplain risk assessment is conducted through several stages. First, rainfall design is chosen based on the frequency distribution having the smallest standard deviation. Second, the unit hydrograph analysis uses short duration and short rainfall observation data from several events using HSS Snyder, SCS, Nakayau, ITB-1 and ITB-2. Model calibration is done by finding the hydrological parameters of the watershed of each model, with the parameter values not referring to the limits specified for each model. Based on the results of the analysis of the coefficient of rainfall-runoff transformation in Dengkeng watershed obtained range for the value of Cp and Ct in Snyder method of 0.297 - 1.002 and 0.871 - 1.061, CN coefficient on SCS 45,246 - 90,205, coefficient α at Nakayasu 0.978 - 5.288, coefficient Cp and Ct at ITB-1 ranged from 0.39 to 4.935 and 0.613 to 0.652 while the coefficient Cp and Ct on ITB-2 ranged from 0.581 to 1.358 and 0.613. Third, conduct a hydraulic analysis to evaluate capacity based on load in the form of discharge and resistance in the form of river capacity. In this study, the analysis of river capacity was carried out at the initial cross-section of downstream flooding of the Dengkeng River. The analysis results show that the cross-sectional capacity of 122.6 m3 / s or flow discharges the annual return period of 1.379. Fourth, mapping and risk analysis based on the maximum water level that occurred during the modeling period, if in step four there is a failure so that the innundation in the floodplain. Flood risk analysis is based on hazard and vulnerability levels, thus indicating that the risk level of Dengkeng watershed has been categorized as very high in the return period of 2 years. Fifth, referring to the flood risk category that occurs then the recommended flood discharge rate plan that describes a certain return period. In Dengkeng watershed is recommended the amount of flood discharge plan using minimum 100 year return period to reduce the risk level to acceptable risk level.